2009
DOI: 10.1118/1.3121488
|View full text |Cite
|
Sign up to set email alerts
|

On the characterization and uncertainty analysis of radiochromic film dosimetry

Abstract: Radiochromic film is a dosimeter of choice in applications requiring high spatial resolution, two dimensional measurements, or minimum perturbation of the beam fluence. Since the measurement uncertainty in Gafchromic film dosimetry is thought to be significant compared to that of ionization chambers, a rigorous method to evaluate measurement uncertainties is desired. This article provides a method that takes into account the correlation between fit parameters as well as single dose values in order to obtain ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
147
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(161 citation statements)
references
References 16 publications
(13 reference statements)
2
147
0
7
Order By: Relevance
“…While the use of reflective mode for the film scanning under Bouchard's protocol is not in common use, reflective mode has been examined in previous papers 20 , 21 to produce comparable results to transmission mode (22) . While one study (23) has suggested a dependence of the dose in an ROI to the pixel intensity of any surrounding film, Mendez et al (21) has not corroborated the finding and believed it may be a scanner‐specific effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the use of reflective mode for the film scanning under Bouchard's protocol is not in common use, reflective mode has been examined in previous papers 20 , 21 to produce comparable results to transmission mode (22) . While one study (23) has suggested a dependence of the dose in an ROI to the pixel intensity of any surrounding film, Mendez et al (21) has not corroborated the finding and believed it may be a scanner‐specific effect.…”
Section: Discussionmentioning
confidence: 99%
“…Other shortcomings were noted in relation to the use of Bouchard's software for film analysis. Since it was initially written for use with the Gafchromic EBT film, only the red channel is used for converting optical densities to dose and its signal saturates at doses higher than 800 cGy (20) . Therefore, the software is not usable for higher doses as with hypofractionated treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fitting procedure and dose uncertainty analysis follow the method described in Bouchard et al ( 19 ) and are summarized here for the sake of completeness. Film calibration is carried out by exposing 12 pieces of radiochromic film to doses from 0 to 800 cGy.…”
Section: Methodsmentioning
confidence: 99%
“…The size of the region of interest (ROI) is chosen according to the dose calculation resolution, and uncertainties with regards to the size of the ROI are carefully considered in the estimations. ( 19 ) The measurements are normalized so the dose is 100% at 1.0 cm depth for phantom A and at 0.5 cm depth for phantoms B and C.…”
Section: Methodsmentioning
confidence: 99%